Association between Iron Tablet Adherence and Anemia among Adolescent Girls - Eva Agustina Yalestyarini; Amanda Ayu Fibrinia; Heri Saputro; Intan Fazrin (Universitas STRADA Indonesia, 2026)
Background: Anemia in adolescent girls can impair growth and development, and iron tablet supplementation is a key strategy to meet iron requirements beyond dietary intake. In this study, respondents were given four iron tablets over one month, taken once weekly. Purpose: The purpose of this research was to examine the relationship between adherence to iron tablet consumption and the incidence of anemia among students at SMPN 1 Wates. Methods: A correlational analytical design with a cross-sectional approach was used, involving a population of 180 individuals and a sample of 124 participants selected through proportional random sampling. Data were collected using observation sheets to assess adherence to iron tablet consumption and to measure hemoglobin levels, and analyzed using a contingency table statistical test. Results: The results showed that the highest proportion of normal hemoglobin levels occurred in the compliant group (92 individuals, 74.2%), while the highest incidence of anemia was found in the non-compliant group (20 individuals, 22.6%). The chi-square test yielded a p-value of 0.000, which is less than α=0.05, indicating a significant relationship between adherence to iron tablet consumption and the incidence of anemia. Conclusion: In conclusion, regular consumption of iron tablets can help adolescent girls prevent anemia, improve learning ability, and enhance nutritional status and overall health, especially when combined with vitamin C–rich foods or beverages that enhance iron absorption.